Proceedings of the ACM SIGCHI Conference on Human Factors in Computing Systems 1997
DOI: 10.1145/258549.258634
|View full text |Cite
|
Sign up to set email alerts
|

The design of a wearable computer

Abstract: The design process used to produce an innovative computer system is presented. The computer system that resulted from the process uses a circular motif both for the user interface and the input device. The input device is a dial and the user interface is visually organized around the concept of a circle. The design process itself proceeded in the presence of a great many constraints and we discuss these constraints and how an innovative design was achieved in spite of the constraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 2 publications
0
23
0
Order By: Relevance
“…Some studies have shown that using a wearable computer to provide such information leads to faster, more efficient performance than using paper 1,2,3 ; whilst other studies have suggested the opposite 18,4 . Further, people using the wearable computer tend to follow the instructions laid out on the display, whereas people using paper tend to adopt a more flexible approach 18,4 .…”
Section: Wearable Computersmentioning
confidence: 99%
“…Some studies have shown that using a wearable computer to provide such information leads to faster, more efficient performance than using paper 1,2,3 ; whilst other studies have suggested the opposite 18,4 . Further, people using the wearable computer tend to follow the instructions laid out on the display, whereas people using paper tend to adopt a more flexible approach 18,4 .…”
Section: Wearable Computersmentioning
confidence: 99%
“…As with mobile computing, a wearable computer user's context is constantly changing. Applications in this area have ranged from understanding sign language [25] to tour guides [26] to airplane maintenance [27]. In all these applications, context has been used to improve the user's experience.…”
Section: Background and Related Workmentioning
confidence: 99%
“…They can support an adapted information flow to the needs of a mobile executive worker, e.g. during the outdoor maintenance of wind turbine generators (WTG), or the indoor maintenance of large passenger aircrafts [1] or for outdoor maintenance in general [2,3].…”
Section: Introductionmentioning
confidence: 99%